(3GdJfHjgGJ GdYdjIs - (3GdYGedj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, J (B966(3g` (B1559(3es ((3eMeO fUjQ Hf TGg eMeO GdcaQGfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdYGdjI ef GdfaS hceGdg aj GdeOQc GdTghOj GdeYHQ Yfg HfhQ GdhdGjI hgh eQJHI ef eQGJH UaGA GdfaSs
(3BNQgG (B:s
(3BNQgG(B: (3hfgGjJg aj GdeTGYQ GdXGgQI hJhMjO GdcKjQ hPde aj GdYde GdMbjbj GdELeGdj GdeJbhe HeG jdj GdLfIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B3: 64s
(3GdPQjYI Edi JUGfja GdTjYI, L (B4: 328s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs